Comparative analysis on pneumatic compact spinning systems. Issue 4 (1st August 2016) - Liu, Xinjin; Zhang, Hong; Su, Xuzhong
Abstract : Purpose: Pneumatic compact spinning is the most widely used compact spinning method at present, in which the negative pressure airflow is used to condense the fiber bundle and decrease the spinning triangle. Compact spinning with perforated drum and lattice apron are mainly two kinds of pneumatic compact spinning now. In the paper, comparative analysis on four kinds of pneumatic compact spinning systems, including two kinds of compact spinning with perforated drum: Rieter's COM4 and Complete condensing spinning (CCS), two kinds of compact spinning with lattice apron: Sussen's Three-line compact spinning (TLCS) and Toyota's Four-line compact spinning (FLCS), were studied. Design/methodology/approach: First, the basic properties of four systems were introduced and comparatively analyzed. Then, the 29.2tex (20S), 14.6tex (40S), 9.7tex (60S) and 7.3tex (80S) combed cotton yarns were spun in the four pneumatic compact spinning systems and ring spinning system respectively. The evenness, breaking strength, and hairiness of spun yarns were tested. Finally, the properties of corresponding woven fabric were tested. Findings: It is shown that comparing to compact spinning with lattice apron, the disposable input cost of compact spinning with perforated drum is higher, but the maintenance cost is lower. Comparing to compact spinning with lattice apron, the evenness of yarn spun by compact spinning with perforated drum is improved whereas the breaking strength is decreased. Furthermore, although harmful long hairiness (≥3mm) of yarn spun by CCS is a little more, the beneficial short hairiness (1-2mm) is also more, which can make the fabric fullness and have better comfortable feeling. Originality/value: In the paper, comparative analysis on four kinds of pneumatic compact spinning systems, including two kinds of compact spinning with perforated drum: Rieter's COM4 and Complete condensing spinning (CCS), two kinds of compact spinning with lattice apron: Sussen's Three-line compact spinning (TLCS) and Toyota's Four-line compact spinning (FLCS), were studied. The basic properties, spun yarn qualities and properties of corresponding woven fabric of four systems were analyzed comparatively.